Effectiveness of Selective Girdling in Enhancing the Growth Performance of Planted Dryobalanops Beccarii Under Reforestation at Gunung Apeng, FR, Sarawak - Lee, Pick Sean (Universiti Malaysia Sarawak, UNIMAS, 2013)
A study on the assessment on the growth performance of planted Dryobalanops beccarii under the reforestation at Gunung Apeng, FR, Sarawak with selective girdling treatment was carried out. The objective of this study was to investigate the suitable silviculture treatment on the growth performance of planted Dryobalanops beccarii under reforestation in Gunung Apeng, FR, Sarawak. In this study, Dryobalanops beccarii were planted in line planting in the study plot 2005 and 2007 were chosen. The height of tree, stem diameter and survival rate were measured. The monitoring period on the growth performance of Dryobalanops beccarii was 60 and 90 days after silviculture treatment were applied. Based on the observation in the field, there were some factors which affected the growth performance of Dryobalanops beccarii which were canopy openness, planting technique and topography of the area. The study showed that the survival rate of Dryobalanops beccarii showed 100 % after silviculture treatment. The result showed that there was significance different of relative growth rate in diameter (RGD) among control, slashing and girdling treatment after 60 days of silviculture treatment and also significance different among control and girdling treatment after 90 days of silviculture treatment in the study plot 2007. Girdling treatment showed the highest RGD in both the study plot 2005 and 2007 which indicated that the effectiveness of the girdling treatment as compared to the control and slashing treatment.